Engineering A Locally-Sourced Adjustable Height Mechanical Creeper for Enhanced Automotive Service Ergonomics (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The study aims to develop a robust adjustment mechanism using locally available materials that provides smooth and reliable height variation.Design/Methodology/Approach: The study adopted the Design for Manufacturing Assembly (DFMA) approach. The creeper was first drawn based on its dimensions, after which it was modelled into a 3D shape using CAD software to provide an enhanced and detailed three-dimensional view of the creeper, aiding its construction. The various parts of the creeper (made up of the main frame, a padded platform mounted on the main frame and caster wheels that support the weight of the creeper and allow it to slide in and out underneath the vehicle) were designed. Stress and safety analyses were performed to ensure the safety and mechanical integrity of the designed creeper.Findings: The design FoS (Factor of Safety) of 1.96 (⁓ 2.0) is within the recommended range. The galvanised steel frame offered the necessary strength and stability to support the mechanic’s weight while remaining lightweight enough for easy handling. The installation of six caster wheels enabled the creeper to glide smoothly on various surfaces, enhancing mobility when positioning the creeper under vehicles.Research Limitation: While the design of the creeper utilising locally produced materials offers numerous strengths, including cost efficiency, sustainability, and local economic support, there may be potential weaknesses, such as material variability, technological constraints, and challenges to market acceptability.Practical Implication: This creeper offers a simple, relatively inexpensive and worthy alternative to cardboards and rugs often used as creepers by artisanal auto mechanics.Social Implication: This technological approach represents a paradigm shift toward inclusive, sustainable, and socially responsible engineering that prioritises local empowerment and community development.Originality/Value: The variable height system incorporates anthropometric data from local populations to optimise ergonomic benefits, moving beyond standard Western anthropometric assumptions.
Keywords: Adjustable. caster wheels. ergonomics. mechanic creeper. variable height